Pelatihan Penelitian Tindakan Kelas untuk Meningkatkan Kompetensi Guru - Hartono, Hartono; Salmaini Yeli (Al-Mu'awanah: Jurnal Pengabdian kepada Masyarakat, 2026)
Classroom Action Research (CAR) is one of the strategic approaches to enhancing teachers' professionalism while continuously improving the quality of learning. However, many teachers still face challenges in understanding the concepts, designing, implementing, and writing research reports and scientific articles based on CAR. This community service program aimed to improve the competence of teachers at MTs Raudhatut Thullab, Siak Kecil District, Bengkalis Regency, in conducting Classroom Action Research. The methods employed included training sessions, discussions, brainstorming activities, case studies, mentoring, and self-directed learning through an electronic CAR module. The program was conducted over three days and involved 19 participants, of whom 17 actively participated in all activities. Evaluation was carried out through observation, discussions, and questionnaires to assess participants’ understanding and perceived benefits. The results indicated an improvement in teachers’ understanding of the principles and procedures of Classroom Action Research, increased awareness of CAR as a professional necessity, and enhanced motivation to innovate in teaching and scientifically document classroom practices. The attendance rate reached 90%, reflecting a high level of participant enthusiasm. Furthermore, participants reported that the training contributed to the enhancement of their pedagogical knowledge, problem-solving skills in learning processes, creativity, and professional competence. Nevertheless, time constraints, differences in participants’ abilities, and limited research experience remain challenges that require follow-up through continuous mentoring programs.